Public procurement, a tool for achieving the goals of sustainable development - Otilia Manta; Mirela Panait; Eglantina Hysa; Elena Rusu; Maria Cojocaru (Amfiteatru Economic Journal, 2022)
This paper proposes a "systematization" of current concerns about sustainable public procurement, an investigation of ways and solutions for public procurement to make an increased contribution to achieving sustainable development goals. The authors emphasize the need to capitalize on all the components of sustainability, especially the social component and those on how to support the public procurement process in compliance with climate change procedures. It is very important for the authorities to take into account the social sustainability of public procurement when awarding contracts by introducing sustainability clauses in public procurement legislation. In order to clarify this issue, the national laws of the countries reporting to the World Bank on public procurement issues have been mapped, the opinions of other researchers have been systematized, as well as relevant studies of international organizations (OECD, European Commission, UNESCO, World Bank). Statistical data from the World Bank's Global Public Procurement Database (GPPD), systematized by group of countries, were processed using statistical tools to test the hypotheses.
Keywords: E6; Q54; F63; 330; climate change; economic development; sustainable public procurement